ENHANCING PEDIATRIC SAFETY: THE CRITICAL ROLE OF NURSES IN FALL PREVENTION AT A YOGYAKARTA PRIVATE HOSPITAL - Rahayu, Margareta Hesti (DPW PPNI Provinsi Jawa Barat, 2024)
Introduction: The incidence of falls that cause serious injuries among patients remains in the list of 10 major patient safety issues. Approximately 63% of falls led to death from 465 reported cases of patients with serious injuries. Methods: This study is qualitative research using a single explanation case study approach. Data were collected through observation, interviews and documentation studies in a pediatric ward in a private hospital in Yogyakarta. Results: Study discovered four themes: family and child characteristics contribute to the fall incidence, fall assessment and education is being implemented, comprehensive fall prevention approach, nurses have responsibility to prevent falls in maintaining the quality of service. Conclusion: Nurses have high level of awareness in performing fall prevention and management.